Etiopathogenesis of aplastic anemia in children: a case control study - Verma, Sanjeev Kumar; Koonwar, Sciddhartha; Kumar, Sarvesh; Nimesh, Nivedita; Siddique, M. K. J.; Kumar, Archana (International Journal of Research in Medical Sciences, 2016)
Background: Aplastic anemia is not an infrequent clinical syndrome that we encounter. In about two thirds of cases of aplastic anemia it is not possible to identify any likely cause. Aim of the study was to study the role of organochlorine compounds, Parvovirus B19, Hepatitis viruses B and C and HIV I and II in causation of aplastic anemia in children. Methods: 25 children of bone marrow biopsy proved aplastic anemia and 25 age Matched controls were investigated for the presence of Parvovirus B19, Hepatitis viruses B and C, HIV I and II and for increased levels of organo-chlorines in blood and bone marrow. ELISA technique to detect antibodies against Parvovirus B19 (IgM), HCV (IgG), HbsAg, HIV I and II was used. Gas chromatography was used to measure blood levels of organo-chlorine compounds α, β, γ, δ HCH, p-p DDE. Results: out of 25 children of aplastic anemia 5 cases (20%) were IgM ELISA positive against Parvovirus B19, 6 cases (24%) were positive for IgG antibody against HCV and 1 case (4%) was Australia antigen positive. 14 cases (56%) showed increased levels (>mean±2SD) of organochlorine compounds α, β, γ, δ HCH, p-p DDE. None of the cases were positive for HIV I and II. None of the controls were positive for Parvovirus B19 (IgM) neither for HCV (IgG). Multiple factors (>1) were positive in 4 cases (16%). 5 cases (20%) didn’t have any positivity for studied factors. 22 cases (88%) of aplastic anemia children were >5 years of age. 21 cases (84%) belonged to rural areas. 11 cases (44%) presented in the month of March and April. Parvovirus B19 was more prevalent (80% cases) in the older age group of children (8-12years). Conclusions: Majority of virological agents contribute to non-severe aplastic anemia. Significant association was found between very severe and severe aplastic anemia with organochlorine compounds. However larger community based studies are needed to correlate this.